2017
DOI: 10.1038/s41598-017-15264-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D supplementation on inflammation and nuclear factor kappa-B activity in overweight/obese adults: a randomized placebo-controlled trial

Abstract: In-vitro studies suggest that vitamin D reduces inflammation by inhibiting nuclear factor kappa-B (NFκB) activity. Yet, no trials have examined the effects of vitamin D supplementation on NFκB activity in-vivo in humans. We conducted a double-blind randomized trial (RCT) examining effects of vitamin D supplementation on inflammatory markers and NFκB activity in peripheral blood mononuclear cells (PBMCs). Sixty-five overweight/obese, vitamin D-deficient (25-hydroxyvitamin D [25(OH)D] ≤ 50 nmol/L) adults were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 58 publications
2
30
0
Order By: Relevance
“…The plasma levels of several inflammatory markers, including IL1β, IL6, IL8, IL10, IL12, IL17, IL18, IL23, IL33, interferon alpha (INFα), and gamma (INFγ), monocyte chemoattractant protein‐1 (MCP‐1), and tumor necrosis factor (TNF), were measured simultaneously in a single sample (25 μL) using a commercial bead‐based multi‐analyte assay (LEGENDplex, Biolegend, CA, USA) as previously described. [ 47 ] Briefly, a kit‐specific protocol on 96‐well plates was performed following manufacturer's instructions. After addition of beads, samples, standards and reagents, plates were incubated in the dark for 2 h at 600 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…The plasma levels of several inflammatory markers, including IL1β, IL6, IL8, IL10, IL12, IL17, IL18, IL23, IL33, interferon alpha (INFα), and gamma (INFγ), monocyte chemoattractant protein‐1 (MCP‐1), and tumor necrosis factor (TNF), were measured simultaneously in a single sample (25 μL) using a commercial bead‐based multi‐analyte assay (LEGENDplex, Biolegend, CA, USA) as previously described. [ 47 ] Briefly, a kit‐specific protocol on 96‐well plates was performed following manufacturer's instructions. After addition of beads, samples, standards and reagents, plates were incubated in the dark for 2 h at 600 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…Pharmacological activation of VDR signaling by a synthetic ligand in combination with a Bromodomain‐containing protein 9, or BRD9 inhibitor is able to partially restore β‐cell function and glucose homeostasis in T2DM mouse models . In line with this, vitamin D supplementation has been reported to improve chronic low‐grade inflammation and diabetic condition in patients with type T2DM . Therefore, targeting VDR signaling highlights great potential for ameliorating chronic metabolic diseases.…”
mentioning
confidence: 85%
“…97,98,100,101 While these have real value in illuminating the functions of the various components of the immune system, due to the complexity of the immune system and how real-world exposures may interact with it, in vivo studies are likely to be more reliable indications of real-world effects. 104 Third, some studies on the effects of oral vitamin D exposure are based on protocols that use modest doses of vitamin D. 105,106 While such studies may be safer for participants than studies with larger doses, a stronger signal on effect will undoubtedly be observed through studies that use larger doses. Table 2 includes some of the effects on the immune system of very high-dose vitamin D supplementation in humans from a non-systematically selected subset of studies in the literature.…”
Section: Select Effects Of Vitamin D On the Immune Systemmentioning
confidence: 99%